Trust and resource oriented communication scheme in mobile ad hoc networks - Khan, Burhan Ul Islam; Olanrewaju, Rashidah Funke; Yusoff, Siti Hajar; Mir, Roohie Naaz; Sanni, Mistura L. (Springer, 2018)
Attaining high security in mobile ad hoc networks (or MANETs) is the utmost concern in the present era of wireless ad-hoc communication and efforts are continuously being made by the researchers, in order to provide a feasible solution for the same. Impervious security has to be ensured in MANETs because of their involvement in transacting highly sensitive information. However, it has been discerned that during the communication process, the decentralized and dynamic nature of MANETs impedes the security of mobile nodes. This study is an attempt to enhance the security in routing techniques of MANETs by overhauling the existing security system after its critical evaluation. It has been observed that the cryptographic techniques in use prove to be inefficient or fail in some of the current scenarios. Therefore, a non-cryptographic method has been put forward that strengthens the process of authenticating nodes in MANETs by taking into account two factors viz. trust and resource, unlike the conventional ones. On analyzing the performance with respect to throughput, packet delivery ratio, end-to-end delay and computational time, the proposed system proves to be better than the previous standard secure routing scheme.